2021
DOI: 10.3171/2020.10.spine201385
|View full text |Cite
|
Sign up to set email alerts
|

Long-segment posterior cervical decompression and fusion: does caudal level affect revision rate?

Abstract: OBJECTIVE Posterior cervical decompression and fusion (PCDF) is a commonly performed procedure to address cervical myelopathy. A significant number of these patients require revision surgery for adjacent-segment disease (ASD) or pseudarthrosis. Currently, there is no consensus among spine surgeons on the inclusion of proximal thoracic spine instrumentation. This study investigates the benefits of thoracic extension in long-segment cervical fusions and the potential drawbacks. The authors compare outcomes in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A large database study of 16,033 patients receiving multilevel (>1 level) ACDF suggested a revision surgery rate of 10.7%. Reoperation rates for adjacent segment disease and pseudarthrosis after 3 or more levels of PCDF have been reported at 4.8% in a retrospective cohort of 369 patients 41. Conversely, in a recent large claims database, revision rates for 3-level PCDF were higher than ACDF (7.9% to 3.6%; P < 0.0001) 42.…”
Section: Discussionmentioning
confidence: 97%
“…A large database study of 16,033 patients receiving multilevel (>1 level) ACDF suggested a revision surgery rate of 10.7%. Reoperation rates for adjacent segment disease and pseudarthrosis after 3 or more levels of PCDF have been reported at 4.8% in a retrospective cohort of 369 patients 41. Conversely, in a recent large claims database, revision rates for 3-level PCDF were higher than ACDF (7.9% to 3.6%; P < 0.0001) 42.…”
Section: Discussionmentioning
confidence: 97%
“…They found that the rate of symptomatic ASD requiring surgery was 0.74 (4/539) in the LMS group versus 1.19 (1/84) in the CPS group without any statistical difference. In 2021, Hines et al26 reported on a combination of LMS and CPS used at C7. In their study, there were 108 patients with PCFs C3–7 that included 71 patients (65.7%) with LMS at C7 and 37 patients (34.3%) with PS at C7.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the studies were comparative 11,27 with LMS and CPS at all cervical levels of the spine or noncomparative [21][22][23][24][25] with either all LMS screws or all CPS or a combination of both. 26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations